How to catch a Mamasaurus - Walstead, Alice; Elkerton, Andy (Naperville, Illinois : Sourcebooks Wonderland, 2024)
The How to Catch Kids try to trap the Mamasaurus, a one-of-a-kind creature whose love, kindness, and awesomeness have no limits.
Ages 4-10.
Grades K-1.
4 and up.
Keywords: Dinosaurs -- Juvenile fiction; Mothers -- Juvenile fiction; Stories in rhyme; Picture books -- Juvenile fiction; Stories in rhyme; Picture books